Common techniques useful to the practicing or training orthopaedic surgeon on call in a pediatric hospital. Issue 3 (May 2018) - Sheffer, Benjamin W.
Abstract : This article highlights surgical procedures with which orthopaedic residents entering a pediatric rotation should be familiar. Closed reduction and percutaneous pinning of supracondylar humeral fractures, in situ pinning of slipped capital femoral epiphysis, and flexible intramedullary nailing of long bone fractures are described. Although these are just a few of many procedures a resident will learn while on a pediatric rotation, they probably are the most utilized while on call at a pediatric hospital.